Analisis Struktur Komparatif Industri pada Perkembangan Industri - Salvia Rahma T.H; Axel Aditya Ramadhan; Muhammad Yasin (Jurnal Kajian dan Penelitian Umum, 2023)
The concept of comparative advantage explains how a country can allocate its resources efficiently in an open economy. The concept of relative advantage also means a measure of potential advantage or competitiveness. This study aims to obtain the results of an analysis of the comparative industrial structure of industrial development. In this study using the literature review method. Four countries have adopted their policies titled Making Indonesia 4.0 Indonesia, Industry 4WRD Malaysia, Industrial Strategy Building a Britain Fit for The Future and “New Industrial Structure” by Japan. Industry 4.0 policies in Indonesia and three other countries can enhance the evaluation of values, human capital, complexity, institutional framework and sustainable resources. Indonesia's policies have not yet achieved AI, health and biotech research priorities while Indonesia has a large domestic market.